2010
DOI: 10.1002/ar.21090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Muscle Fiber Types in the Perivertebral Musculature of Two Different Sized Species of Mice

Abstract: Many physiological parameters scale with body size. Regarding limb muscles, it has been shown that the demands for relatively faster muscles, less postural work, and greater heat production in small mammals are met by lower proportions of Type I and conversely higher proportions of Type II fibers. To investigate possible adaptations of the perivertebral musculature, we investigated the proportion, spatial distribution, and cross-sectional area (csa) of the different muscle fiber types in the laboratory and har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 97 publications
(117 reference statements)
3
30
1
Order By: Relevance
“…They described a multifidus muscle originating from the transverse process and spanning four vertebrae to attach to the spinous process of the fourth vertebrae craniad, and the rotatores muscles are described as spanning only one vertebral level. This indicates that Hesse et al (2010) found no TSP muscle fibers spanning two or three vertebral levels, and therefore the observations in these mouse species differ from the results of our investigation. Although we also found that some TSP muscles spanned four vertebral segments, our specimens also had muscle fibers spanning one, two, three, and four vertebral levels.…”
Section: Discussion Morphologycontrasting
confidence: 99%
See 3 more Smart Citations
“…They described a multifidus muscle originating from the transverse process and spanning four vertebrae to attach to the spinous process of the fourth vertebrae craniad, and the rotatores muscles are described as spanning only one vertebral level. This indicates that Hesse et al (2010) found no TSP muscle fibers spanning two or three vertebral levels, and therefore the observations in these mouse species differ from the results of our investigation. Although we also found that some TSP muscles spanned four vertebral segments, our specimens also had muscle fibers spanning one, two, three, and four vertebral levels.…”
Section: Discussion Morphologycontrasting
confidence: 99%
“…Our observations of the attachment points of the MLC3F-nlacZ mouse TSP muscles correlate well with the general pattern reported in some species of mice (M. musculus and Micromys minutus) (Hesse et al, 2010) and other mammals (Slijper, 1946;Brink and Pfaff, 1980;Stubbs et al, 2006), with muscles existing in the space between the transverse and spinous processes and attaching in a regular, repeated pattern to bony sites throughout the lumbar spine.…”
Section: Discussion Morphologysupporting
confidence: 89%
See 2 more Smart Citations
“…3C–D). Additionally, SMA vulnerable slow twitch muscles like the QL 24 did not express parvalbumin (Supplementary Fig. 4).…”
Section: Resultsmentioning
confidence: 99%